2013
DOI: 10.1007/128_2013_466
|View full text |Cite
|
Sign up to set email alerts
|

Sialic Acid Receptors of Viruses

Abstract: Sialic acid linked to glycoproteins and gangliosides is used by many viruses as a receptor for cell entry. These viruses include important human and animal pathogens, such as influenza, parainfluenza, mumps, corona, noro, rota, and DNA tumor viruses. Attachment to sialic acid is mediated by receptor binding proteins that are constituents of viral envelopes or exposed at the surface of non-enveloped viruses. Some of these viruses are also equipped with a neuraminidase or a sialyl-O-acetyl-esterase. These recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
278
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 232 publications
(280 citation statements)
references
References 198 publications
(229 reference statements)
1
278
0
1
Order By: Relevance
“…Influenza viruses bind to sialylated macromolecules, often with a preference for either a2,3-or a2,6-linked sialic acid (Matrosovich et al, 2013). Recognition of this linkage type may vary substantially depending on the context of the oligosaccharide containing this sugar in a terminal position (Sauer et al, 2014;Stevens et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Influenza viruses bind to sialylated macromolecules, often with a preference for either a2,3-or a2,6-linked sialic acid (Matrosovich et al, 2013). Recognition of this linkage type may vary substantially depending on the context of the oligosaccharide containing this sugar in a terminal position (Sauer et al, 2014;Stevens et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Another ganglioside, GD1a, binds polyoma viruses, including the human pathogens, JC and BK viruses (14,15), and the E. coli toxin LT-IIB (60), and, like asialoGM1, can also function as a coreceptor for TLR2 (30). Another important class of respiratory pathogens, influenza viruses, bind to airway ECs through interaction of the viral HA protein with SA residues of glycoproteins and gangliosides (33). In the present studies, NEU3 was localized to superficial epithelia and the ciliated brush border (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The human airway epithelial surface is decorated with glycoconjugates expressing SA connected to underlying sugars in ␣-2,3 and ␣-2,6 linkages (12). These sialylated glycoconjugates include specific receptors that respond to danger signals (9), serve as binding sites for pathogenic bacteria and viruses (23,31,33), and initiate epithelial repair programs (9). Superimposed on this highly sialylated EC surface is a constantly moving, SA-rich mucous blanket (50).…”
mentioning
confidence: 99%
“…To date, several viruses, e.g. influenza virus or polyomaviruses, have been shown to bind specifically to sialic acid present on the surface of target cells, whilst its possible role in EHV-1 infection has not yet been described (Matrosovich et al, 2015). We found that removal of sialic acid residues from cells inhibited EHV-1 infection of CD172a + cells by 90-100 %.…”
Section: Discussionmentioning
confidence: 52%